Transformasi Pembelajaran di Sekolah Kejuruan: Meningkatkan Literasi Digital Melalui Inovasi pembelajaran - Anggana, Bima; Kurniawan, Wahyu; Syafiq, Abdullah (Universitas Sarjanawiyata Tamansiswa, 2024)
This research was conducted with the aim of analyzing whether the application of the problem-based learning model can improve students' digital literacy skills. Another purpose of this study is to describe the success rate of the problem-based learning model in order to improve digital literacy skills. The experimental research design used in this study is in the form of a nonequivalent control group design. In this study, there will be two groups that are not randomly selected. Both were then given a pretest to find out the initial state and differences between the experimental group and the control group. A good pretest result is when the values of the experimental group in the control group do not differ significantly. The sample was 36 students in the experimental group and 36 students in the control group. Overall, while PBL shows potential to improve digital literacy, several key factors may limit the rate of such improvement. These factors include the relevance and complexity of the problem used, intrinsic motivation and student engagement, access to and quality of digital resources, and advanced digital literacy skills.